Behavior of Built-Up Shear Links Under Large Cyclic Displacement - Itani, A.M.; Elfass, S.; Douglas, B.M. (Engineering Journal, 2003)
The towers of the Richmond-San Rafael Bridge (RSRB) play a significant role in the overall bridge seismic behavior and performance. They are responsible for transferring the inertia forces that are generated in the superstructure to the foundation during an earthquake. Therefore, the components of these towers lie in the direct seismic load path and thus any premature failure in these members will interrupt the load path causing inadequate seismic behavior. This paper summarized the results of an experimental investigation of two built-up shear links. As expected, the shear dominated the behavior of the two built-up links. The plastic rotational capacity for the two links exceeded the code specified values for such configurations.